Legionnaires' disease in transplant recipients: A 15‐year retrospective study in a tertiary referral center. Issue 5 (28th September 2017) - Sivagnanam, Shobini; Podczervinski, Sara; Butler‐Wu, Susan M.; Hawkins, Vivian; Stednick, Zach; Helbert, Lois A.; Glover, William A.; Whimbey, Estella; Duchin, Jeffrey; Cheng, Guang‐Shing; Pergam, Steven A.
Abstract: Legionnaires' disease (LD) can be fatal among high‐risk transplant recipients. To understand the epidemiology of LD, we reviewed 15‐year longitudinal data from a center in Seattle, Washington that cares for both solid organ transplant (SOT) and hematopoietic cell transplant (HCT) recipients. We identified all laboratory‐confirmed LD and extracted data on species, diagnostic modalities, clinical presentation, management, and outcomes from medical records. Among 32 patients with LD, transplant recipients made up the majority of diagnoses (22, 69%; SOT 10, HCT 12). Approximately 0.8% of transplant recipients who underwent Legionella‐ specific testing were positive. Non‐ pneumophila Legionella species (LNLP), which are not detected by urinary antigen test, accounted for half the cases, led by Legionella micdadei (32%). The severity and outcome between Legionella pneumophila and LNLP infections were similar (attributed mortality, 36% vs 27%); all LNLP deaths occurred in transplant recipients with L. micdadei . The clinical and radiological features mimicked other opportunistic pathogens; 32% (n=7) were not on empiric treatment at the time of diagnosis. These data add to the emerging literature describing the importance of LD and highlight the need for both routine Legionella testing on transplant recipients with pulmonary findings and empiric Legionella ‐active antibiotic therapy.